2020
DOI: 10.21834/ebpj.v5isi3.2548
|View full text |Cite
|
Sign up to set email alerts
|

The Utilisation of LEGO and Other Materials as Prototyping Tools in the Co-Creation Process

Abstract: This paper aims to investigate the usefulness of LEGO and other materials as prototyping tools in the co-creation process involving multiple stakeholders. The results demonstrate that using LEGO and other materials as prototypes in the co-creation process helps designers and stakeholders to explore, evaluate and modify ideas three-dimensionally to validate design solutions, idea generation and evaluation.  This study believes that  LEGO and other materials are efficient co-design prototyping tools to ensure it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Here, we can see that majority of respondents strongly agree and agree that prototypes using LEGO and other low-fidelity materials can be used as a tool to facilitate communication and engagement among team members and stakeholders. Here we can see that the possibility of combining LEGO with other materials, which are easily mouldable and transformable, may reveal design problems more quickly, and accurately so that reflective, iterative, and interpretative solution finding (Isa and Liem, 2020;Ranscombe et al, 2020), as well as facilitate teamwork.…”
Section: Legos and Low-fidelity Materials Benefits Multidisciplinary ...mentioning
confidence: 95%
See 2 more Smart Citations
“…Here, we can see that majority of respondents strongly agree and agree that prototypes using LEGO and other low-fidelity materials can be used as a tool to facilitate communication and engagement among team members and stakeholders. Here we can see that the possibility of combining LEGO with other materials, which are easily mouldable and transformable, may reveal design problems more quickly, and accurately so that reflective, iterative, and interpretative solution finding (Isa and Liem, 2020;Ranscombe et al, 2020), as well as facilitate teamwork.…”
Section: Legos and Low-fidelity Materials Benefits Multidisciplinary ...mentioning
confidence: 95%
“…This indicates that participants were comfortable when using LEGO and Low-fidelity Materials as tools in the idea-generation activities. Thus, it can be concluded that LEGO and low-fidelity materials may enhance creativity and encourage users to develop their ideas together (Peters & Ahmadpour, 2020;Isa & Liem, 2020;Van Waart, et al, 2015).…”
Section: Legos and Low-fidelity Materials Benefits Multidisciplinary ...mentioning
confidence: 99%
See 1 more Smart Citation